PRIMARY ACRODERMATITIS ENTEROPATHICA - DR RUGMINI KAMALAMMAL,; DR. S. SANTHA KUMAR,; DR. GUNASEKARAN ANANDAN,; DR. ABDUL AZIZ.A,; DR. SANGEETHA HARIPRASATH, (International Journal of Pharma and Bio Sciences, 2014)
Acrodermatitis Enteropathica is characterized by erythematous patches , plaques, pustular and bullous lesions with acral and periorificial distribution, diarrhoea and abnormally low Zinc levels. We are presenting a baby with the characteristic rash, failure to thrive and diarrhea with reduced levels of Zinc. The baby was treated initially for lactose intolerance but lesions did not subside. There was complete resolution with therapeutic dose of Zinc supplementation and emollients. The mother’s serum zinc levels were extremely low suggesting a diagnosis of primary Acrodermatitis Enteropathica. The case is being presented for highlighting the rare primary form of Zinc deficiency and its dermatological features.